Research on school effectiveness and school improvement as a driver for the increase of educational quality in Latin America - F. Javier Murillo (Universidad Autónoma de Madrid, 2015)
The evaluations carried out by national and international organizations have paid off: we have already scientifically certified that the performance of our students in Language or Mathematics is lower than we would like. Unfortunately, this data does not represent more than the tip of the iceberg, under water is submerged a set of difficulties that accompany our educational systems and whose overcoming is the real challenge that we face every day all of us who are dedicated to Education . And that challenge has a name: raise the levels of educational quality and equity, if there is any possibility of separating both terms.